Digital India and Rural Banking Transformation: An Assessment of Financial Inclusion Outcomes - Rupesh Anil Kasar ,Dr. Sanjay S. Kanode, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Digital India mission has become a transformer in the landscape of Indian rural banking bycreating a digital environment with financial literacy and technology-driven financial services. In this study, the effect of Digital India on the rural banking